Speech and language delay in childhood: a retrospective chart review* - Yasin, Ahmet; Aksu, Hatice; Özgür, Erdoğan; Gürbüz Özgür, Börte (ENT Updates, 2017)
Objective: Speech delay should be considered in a child in case of not demonstrating the stages of language development in accordance with general developmental period or compared to the peers. Speech delay often may be a sign of a variety of mental and somatic diseases rather than a diagnosis. In this study, we aimed to investigate the demographic characteristics, psychiatric diagnoses and factors that play a role in speech delay in patients admitted to a child psychiatry outpatient clinic with a complaint of speech delay. Methods: Medical records of the patients who were admitted to the child and adolescent psychiatry outpatient clinic with complaints of “not talking”, “speech delay”, “language delay”, “not forming a sentence” between November 1, 2014 and October 31, 2015 were retrospectively evaluated. Results: Of a total of 127 cases, 22.8% were female and 77.2% were male. The mean age was determined as 3.1±1.1. Average duration of TV, tablet and smart phone exposure was 5.3±3.4 hours per day. Only 14.1% of cases were going to preschool education, primary school or special education. It was found that 38.2% were not presence in an environment where allows peer relationship; bilingualism history was present in 3.1%; 23.6% had a family history of speech delay, and 21.6% of cases had no meaningful words. Developmental language delay (28.18%) as a clinical finding and pervasive developmental disorders (PDD) as a psychiatric disorder (23.64%) were the most frequent diagnoses. There were no statistically significant differences between PDD and other patients when compared in terms of TV and other virtual media exposure duration [t(55)=1.58, p=0.12]. Conclusion: Different diagnoses lie under the complaint of speech delay. We emphasize that it is important to evaluate these patients multidisciplinary and refer to child and adolescent mental health experts for detection of probable psychopathology and establishing the appropriate treatment plan at an early stage.